2005
DOI: 10.4315/0362-028x-68.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an On-Line Hide Decontamination Procedure for Use in a Commercial Beef Processing Plant

Abstract: The hides of cattle are the source of Escherichia coli O157:H7 that contaminates beef carcasses during commercial beef processing. Therefore, effective interventions that reduce hide contamination should reduce subsequent carcass contamination. The first objective of this study was to identify the most effective reagents for decontamination of beef hides. Cattle hides draped over barrels were used for in vitro experiments to compare the efficacy of washes using 1.6% sodium hydroxide, 4% trisodium phosphate, 4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
82
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 21 publications
2
82
0
3
Order By: Relevance
“…In a study done by , the carcass contamination rates during processing could not be accounted for by the fecal prevalence of Escherichia coli O157:H7, but could be accounted for by hide prevalence. Bosilevac et al (7,8) and Nou et al (20) extended these findings by demonstrating that antimicrobial interventions targeting cattle hides lead to drastic reductions in the rates of carcass contamination with E. coli O157:H7.Because hide is the main source of carcass contamination, it is crucial to minimize the amount of E. coli O157: H7 on cattle hides before slaughter. Cattle can shed E. coli O157:H7 in their feces at concentrations as high as 10 6 CFU/g (24).…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…In a study done by , the carcass contamination rates during processing could not be accounted for by the fecal prevalence of Escherichia coli O157:H7, but could be accounted for by hide prevalence. Bosilevac et al (7,8) and Nou et al (20) extended these findings by demonstrating that antimicrobial interventions targeting cattle hides lead to drastic reductions in the rates of carcass contamination with E. coli O157:H7.Because hide is the main source of carcass contamination, it is crucial to minimize the amount of E. coli O157: H7 on cattle hides before slaughter. Cattle can shed E. coli O157:H7 in their feces at concentrations as high as 10 6 CFU/g (24).…”
mentioning
confidence: 66%
“…The results of this study indicate that transport to and lairage at processing plants can lead to increases in the prevalence and degree of E. coli O157:H7 contamination on hides and the number of E. coli O157:H7 pulsed-field gel electrophoresis types associated with the animals. More study is needed to confirm the mechanism by which additional E. coli O157:H7 strains contaminate cattle hides during transport and lairage and to design interventions to prevent this contamination.Recent work has revealed that the major source of beef carcass contamination is cattle hides (4,7,8,20). In a study done by , the carcass contamination rates during processing could not be accounted for by the fecal prevalence of Escherichia coli O157:H7, but could be accounted for by hide prevalence.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…En los frigoríficos de todo el mundo se realizan actividades sistemáticas dirigidas a reducir la carga de ECvt-SUH. Las más frecuentes, ya sea de forma individual o combinada, son la aspiración, la pasteurización por vapor y el lavado con soluciones orgánicas de ácido lác-tico, ácido peracético o ácido acético (35)(36)(37). Esta última técnica se destaca debido a su bajo costo, fácil aplicación e inocuidad para la salud pública (37).…”
Section: Análisis De Escenariosunclassified
“…Por otra parte, los ácidos orgánicos permiten reducir la carga de ECvt-SUH, pero no la frecuencia, es decir, si no se controla el número de animales que ingresan al faenado con ECvt-SUH en las heces, el impacto de esta medida sería limitado (36,37,49). La principal desventaja que podría generar el duchado de las canales con ácidos orgánicos son los cambios indeseables en el color de la carne: una mayor luminosidad y tonalidad e inferior índice de decoloración (50); esto favorece el rechazo por parte de los consumidores dada las exigencias en la cultura gastronómica del país (51).…”
unclassified